2004
DOI: 10.1002/jnr.20200
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles for neuropeptide Y Y1 and Y5 receptors in anxiety and sedation

Abstract: Central administration of neuropeptide Y (NPY) causes both anxiolysis and sedation. Previous studies suggest that both effects are mediated via NPY Y1 receptors. However, most of these studies were carried out before the advent of specific NPY receptor ligands. Therefore, a potential role for other NPY receptors in anxiety and sedation remains a possibility. In the present study, we addressed this issue by testing the effects of intracerebroventricular (i.c.v.) injection of NPY as well as specific receptor ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 34 publications
(66 reference statements)
6
70
0
1
Order By: Relevance
“…Consistent with the result from the literature on Mn (Oszlanczi et al, 2010), our data suggested that chronic treatment with AgNPs exerted an increase in the resting time as well as a decrease in the moving distance and moving velocity, revealing the depletion of horizontal activity in the rats. The difference of the rearing frequency between AgNPs-treated rats and the controls demonstrated that AgNPs exerted an inhibitory effect on the vertical exploratory behavior of animals, which was in line with preceding reports on the rats with sedation treatment (Sorensen et al, 2004). Some other indexes such as the number of entries into the center showed the similar down-regulating trend upon AgNPs exposure, indicating AgNPs were able to cause impairment of spontaneous behavior in rats.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the result from the literature on Mn (Oszlanczi et al, 2010), our data suggested that chronic treatment with AgNPs exerted an increase in the resting time as well as a decrease in the moving distance and moving velocity, revealing the depletion of horizontal activity in the rats. The difference of the rearing frequency between AgNPs-treated rats and the controls demonstrated that AgNPs exerted an inhibitory effect on the vertical exploratory behavior of animals, which was in line with preceding reports on the rats with sedation treatment (Sorensen et al, 2004). Some other indexes such as the number of entries into the center showed the similar down-regulating trend upon AgNPs exposure, indicating AgNPs were able to cause impairment of spontaneous behavior in rats.…”
Section: Discussionsupporting
confidence: 90%
“…Although we did not demonstrate causality, only association of NPY with behavioral effects, multiple studies have already determined anxiolytic effects of NPY (for a review, see Heilig, 2004). Increased NPY expression or NPY administration is associated with anxiolytic effects, whereas decreased NPY expression or blockade of its receptors is anxiogenic (Bannon et al, 2000;Heilig and Murison, 1987;Sajdyk et al, 1999;Sorensen et al, 2004;Tschenett et al, 2003). Accordingly, increased NPY expression in the hippocampus after prenatal betamethasone exposure is congruent with anti-anxiety effects.…”
Section: Technical Considerationsmentioning
confidence: 54%
“…The effect of [D-His 26 ]-NPY on nicotine withdrawal was investigated as this compound, in contrast to NPY, has a low affinity for the Y5 receptor (NPY, Ki of 0.28 nM for Y1, Ki of 1.5 nM for Y5; ]-NPY, Ki of 2.0 nM for Y1, Ki of 34.6 nM for Y5) (Mullins et al, 2001). Activation of the Y5 receptor has been suggested to mediate NPY's sedative effects while NPY's anxiolytic and antidepressant-like effects have been suggested to be mediated via the activation of the Y1 receptor (Ishida et al, 2007;Redrobe et al, 2002a;Sorensen et al, 2004). Experiment 1 and 2 indicated that NPY and [D-His 26 ]-NPY elevated the brain reward thresholds of the saline-treated control rats.…”
Section: Introductionmentioning
confidence: 98%